The Anch'Or Harpoon Technique With a Manually Expandable Stentretriever (Tigertriever 13), a Technical Note - Wang, Maud; Elens, Stephanie; Bonnet, Thomas; Halut, Marin; Suarez, Juan Vazquez; Mine, Benjamin; Lubicz, Boris; Guenego, Adrien (Frontiers in Neurology, 2022)
Background and Purpose: Stent and balloon anchor techniques have been described to obtain distal support and straighten catheter loops, stabilize microcatheters in giant aneurysms or access distal tortuous anatomy during thrombectomy. These techniques require catheterization of distal arteries with a microcatheter but tortuosity and length issues may render it challenging, precluding the distal unsheathing of a classical auto-expandable stentretriever with the anchor technique. Methods: We therefore developed the so-called Anch’Or Harpoon Technique using a manually expandable stentretriever, the Tigertriever 13 (Rapid Medical, Yoqneam, Israel). Here, the stentretriever is not unsheathed but pushed out of the microcatheter, advanced as far as possible before manual opening. Results and Conclusion: This technique may be used in 2 different situations. First, in case of vessel tortuosity if the microcatheter can’t be advanced as far as the physician wants: the Tigertriever 13 can be delivered through the microcatheter without having to unsheathe it, be advanced and opened distally to its microcatheter to establish a stable anchor prior to advancing the guiding, intermediate and micro-catheters (anchor technique). The second situation is when distal occlusions lead to length issues, the microcatheter may be too short to cross a distal clot: the Tigertriever 13 can then be pushed out of the microcatheter, and be used to cross a sub-occlusive clot as it has a soft shaped distal tip and the physician sees the artery beyond the sub-occlusion. Then, the Tigertriever will be manually expanded through the clot, and retrieved (harpoon technique) to obtain a recanalization.